Policing in America - Harris, Duchess; Buckey, A. W. (Special reports., 2021)
Explores police officer careers, discussing education, training, and daily duties. Also examines political and social issues related to police work, such as targeting persons of color, police reform, and defunding police departments. Includes photographs, sidebars, a glossary, and further resources.